Age-dependent changes in the anatomical and histological characteristics of the aggregated lymphoid nodules in the stomach of Dromedary camels (Camelus Dromedarius) - Zubieda Ibrahim Hassan Omer; Jia Lu; Yu-Jiao Cheng; Pei-Xuan Li; Zhi-Hua Chen; Wen-Hui Wang (PLoS ONE, 2023)
Gastrointestinal associated lymphoid tissue (GALT) is an important component of the mucosal immune system. It is the largest mass of lymphoid tissues in the body and makes up more than 70% immune cells of entire body. GALT is considered to be the origin of systemic mucosal immunity and consists of solitary lymphoid nodules, aggregated lymphoid nodules (Peyer’s patches, PPs), scattered lymphoid tissues, and follicular associated epithelia. PPs play important roles as antigen inductive sites of the mucosal immune system, which are mainly distributed in the intestine of animals and humans (especially ileum and appendix). However, a special area of well-developed aggregated lymphoid nodules in the abomasum of Dromedary camel was found in our laboratory. Its existence was rarely described in the stomach before. In the present study, we investigated this special structure with the dromedary camels of different ages (young, 0.5–2 years; pubertal, 3–5 years; middle-aged, 6–16 years; old, 17–20 years), by the anatomical, histological and immunohistochemical approaches. The results showed that the special structure was mainly distributed in the cardiac glandular area of the abomasum, forming a triangular area. The mucosal folds in this area were significantly thicker than those in the surrounding region. These mucosal folds had two different forms, namely reticular mucosal folds (RMF) and longitudinal mucosal folds (LMF). There were abundant lymphoid nodules in the submucosa of RMF and LMF, which were arranged in one or multiple rows. The statistical analysis of the height and thickness of RMF and LMF showed that the structure was most developed in pubertal dromedary camels. The histological characteristics of the structure were the same as PPs in the intestine of the Dromedary camel, while anatomical appearance showed some difference. The immunohistochemical examination revealed that both immunoglobulin A (IgA) and G (IgG) antibodies-producing cells (APCs) were extensively distributed in the gastric lamina propria (LP) in all age group. Our finding suggest that camel stomach not only performs digestive functions, but also involves parts of body immunity.